Design of Low Power and Low Area Passive Sigma Delta Modulators for Audio Applications - Fouto, David; Paulino, Nuno (SpringerBriefs in Electrical and Computer Engineering, 2017)
This book presents the study, design, modulation, optimization and implementation of low power, passive DT-ΣΔMs for use in audio applications. The high gain and bandwidth amplifier normally used for integration in ΣΔ modulation, is replaced by passive, switched-capacitor branches working under the Ultra Incomplete Settling (UIS) condition, leading to a reduction of the consumed power. The authors describe a design process that uses high level models and an optimization process based in genetic algorithms to achieve the desired performance.